Analysis of Flood Hazards in Premiere Hills Housing and Surroundings Using the Weighted Overlay Method, Sungai Kunjang District, Samarinda City - Farid, Muh; Septyandy, Muhammad Rizqy; Heriyanto, Heriyanto (JURNAL TEKNIK GEOLOGI : Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
This research was conducted in Sungai Kunjang District, Samarinda City, East Kalimantan Province. Based on the regional geology of Samarinda, this location is included in the stratigraphy of the Kutai Basin with the Balikpapan and Balang Island Formations. This research focuses on determining the flood hazard areas around the Premiere Hills housing complex. The research method used is weighted overlay using spatial analysis, which overlays several maps related to factors that influence vulnerability assessment. The analytical tool used is the Geographic Information System (GIS). Each parameter is given a weight by scoring each parameter, namely land use, elevation, river buffer, rainfall, soil type, and slope slope. An overlay is carried out to obtain the classes of flood hazards. Then, field verification is carried out to determine whether the areas on the flood hazard map match those in the field, especially in areas with a high level of flood hazard. In the analysis results obtained using the weighted overlay method, the research area has a relatively high level of flood danger, which can be seen on the hazard map, where the colour red dominates compared to areas that have a low or medium level of flood danger, which are marked with green and yellow on the map. Based on the analysis results of areas with high flood hazards, verification is carried out to see whether the areas with high flood hazards follow those in the field. It can be seen from this verification that three points are taken, which are areas where flooding often occurs, characterized by low elevation and have poor drainage channels that prevent water from flowing properly